The Effects of L-citrulline Supplementation on the Athletic Performance, Physiological and Biochemical Parameters, Antioxidant Capacity, and Blood Amino Acid and Polyamine Levels in Speed-Racing Yili Horses - Li, Peiyao; Sun, Shuo; Zhang, Wenjie; Ouyang, Wen; Li, Xiaobin; Yang, Kailun (Animals (Basel), 2024)
The objective of this study was to evaluate the effects of pre-exercise L-citrulline supplementation on the athletic performance of Yili speed-racing horses during a high-intensity exercise. On the 20th day of the experiment, blood samples were collected at 3 h and 6 h post-supplementation to measure the amino acid and polyamine concentrations. On the 38th day of the experiment, the horses participated in a 2000 m speed race, and three distinct blood samples were gathered for assessing blood gases, hematological parameters, the plasma biochemistry, antioxidant parameters, and NO concentrations. The results indicate that the L-citrulline group showed a significant increase in the plasma citrulline and arginine concentrations. Conversely, the concentrations of alanine, serine, and threonine were significantly decreased. The glycine concentration decreased significantly, while there was a trend towards an increase in the glutamine concentration. Additionally, the levels of putrescine and spermidine in the plasma of the L-citrulline group were significantly increased. In terms of exercise performance, L-citrulline can improve the exercise performance of sport horses, significantly reduce the immediate post-race lactate levels in Yili horses, and accelerate the recovery of blood gas levels after an exercise. Furthermore, in the L-citrulline group of Yili horses, The levels of the total protein of plasma, superoxide dismutase, catalase, and lactate dehydrogenase were significantly increased both 2 h before and 2 h after the race. The total antioxidant capacity showed a highly significant increase, while the malondialdehyde content significantly decreased. In the immediate post-race period, the creatinine content in the L-citrulline group significantly increased. In conclusion, this study demonstrates that L-citrulline supplementation can influence the circulating concentrations of L-citrulline and arginine in Yili horses, enhance the antioxidant capacity, reduce lactate levels, and improve physiological and biochemical blood parameters, thereby having a beneficial effect on the exercise performance of athletic horses.